2019
DOI: 10.1088/1757-899x/639/1/012040
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Compound Extraction from Industrial Tomato Waste by Ultrasound-Assisted Extraction

Abstract: The tomato fruits have been reported that it contained high nutrient and bioactive compounds. The various Ultrasound-Assisted Extraction (UAE), including extraction temperature of 30, 50 and 70oC and extraction time of 10, 30 and 50 min, were performed in order to extract phenolic compound from tomato waste from industry. The total phenolic compound, total flavonoid content and also retained carotenoid in obtained extract were determined. Moreover, the DPPH radical scavenging activity of extract were studied. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Tomato fruits (Solanum lycopersicum L.) are healthy plants, which can be consumed as a fresh vegetable or can be processed and made into many food products, such as ketchup, paste, sauce, and juice [1]. A tomato which cultivated in the world has been used for produce tomato food products for almost 40 million tons in 2021 [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomato fruits (Solanum lycopersicum L.) are healthy plants, which can be consumed as a fresh vegetable or can be processed and made into many food products, such as ketchup, paste, sauce, and juice [1]. A tomato which cultivated in the world has been used for produce tomato food products for almost 40 million tons in 2021 [2].…”
Section: Introductionmentioning
confidence: 99%
“…A tomato which cultivated in the world has been used for produce tomato food products for almost 40 million tons in 2021 [2]. Tomato waste from commercial tomato manufacturing has been used as raw material for the extraction of bioactive compounds, such as lycopene extraction [3,4], phenolic extraction [1], and pectin extraction [5][6][7]. Grassino et al [6] extracted pectin from tomato peels by reflux at 90 • C for 24 and 12 h and ammonium oxalate/oxalic acid used as solvent.…”
Section: Introductionmentioning
confidence: 99%
“…[ 96 ], who reported the DPPH radical scavenging activity of litchi seed under the optimal UAE extraction time of 45 min. In another investigation, Sengkhamparn and Phonkerd [ 97 ] reported that the UAE extraction time for 50 min showed the highest antioxidant activity (DPPH radical scavenging activity) from industrial tomato waste. Similarly, Nag and Shit [ 98 ] found that the UAE extraction time of 41.45 min was optimal for the DPPH radical scavenging activity from pomegranate peels.…”
Section: Resultsmentioning
confidence: 99%
“…Extractions have also been performed by sonication (SAE) or with microwaves (MAE), to generate fractions with antioxidant properties [14]. Sonication was applied to media containing ethanol 95°(50 min) [15], sunflower oil (10 min, 70 W) [16] or n-hexane:acetone (100 W, 30 min) [17]. Micro-waves (300 W) were used with ethanol 95°(60 s) for the extraction of several metabolites from TP [18].…”
Section: Introductionmentioning
confidence: 99%